A Qualitative Investigation on How Medical Personnel View Their Supportive Role for Cancer Patients - shoshan, Mohamed; Alanazi, Noor Awad; Alqahtani, Norah Farraj; Alsobhi, Mansour Barakatllah Khm; Alahmadi, Saeed MEsfer; Hashim, Hani Mohammed Abohashem Abu; alhamdan, Faisal khalifa ahmad; gaber, Mervat Ali Mostafa; Elfeky, Amany M; Albraik , Layan (Journal of Ecohumanism, 2024)
Physical activity has been recognized as a key component in improving health outcomes for individuals undergoing cancer treatment. However, despite evidence supporting its benefits, discussions about physical activity are not routinely incorporated into cancer care. Healthcare professionals (HCPs) often hesitate to introduce the topic due to a lack of training and evidence-based resources. This study explores the perspectives of both HCPs and cancer patients regarding the integration of physical activity into routine care, identifying challenges and potential solutions to improve adherence.A qualitative study was conducted using semi-structured interviews with cancer patients and HCPs. Participants were recruited through a purposive sampling approach, and interviews were conducted virtually or via telephone. Data were analyzed using thematic analysis to identify recurring themes regarding the promotion and implementation of physical activity in oncology care.Findings revealed that physical activity is not consistently discussed with all cancer patients, with most conversations being patient-initiated. HCPs expressed reluctance to address physical activity due to limited training, lack of resources, and concerns about patient safety. Patients favored self-managed, home-based activity programs over structured exercise sessions in public settings. Both groups identified the need for digital resources, including mobile applications, to facilitate adherence. HCPs emphasized that brief, repeated conversations throughout the treatment pathway would be more effective in promoting behavior change. Additionally, they highlighted the importance of structured training modules to enhance their ability to guide patients effectively.Integrating physical activity into routine cancer care requires structured training for HCPs, access to evidence-based resources, and flexible, self-managed exercise options for patients. Mobile applications and remote tools can serve as scalable solutions to support adherence while minimizing disparities in access to physical activity guidance. Encouraging brief but repeated discussions throughout the care continuum may help normalize physical activity as part of cancer treatment, ultimately improving patient outcomes.